Quantification and characterization of plastics in near-shore surface waters of Atlantic Canada. (August 2022) - Smith, Ariel; Liboiron, Max; Charron, Louis; McIntyre, Jessie; Hawkins, Kaitlyn; McLean, Katie; Peddle, Sheldon; Moore, Greg; Walzak, Mary Jane; Goodman, Alexa; Fulton, Leah; Fredericks, Shanna; et al.
Abstract: Plastics are a ubiquitous pollutant in the marine environment. Despite growing concerns, quantitative and qualitative data on microplastics in aquatic and marine environments of Atlantic Canada is just emerging. Surface water plastics were measured and categorized by morphology (thread, microfibre, fragment, foam, film, pellet, and microbead) in two locations in Nova Scotia and one in Newfoundland and Labrador, Canada. All sites within the three locations contained plastic with an average abundance of 9669 items/km 2 . Most plastics (68 %) were sized as microplastics (0.425–5 mm), and plastic fragments were the most common morphological type. Polyethylene accounted for a third (30 %) of all particles found across all three locations, followed by polypropylene (23 %). Results can inform future research for community-based environmental groups, government, and academia. Highlights: Baseline assessment of microplastic pollution in two Atlantic Canadian provinces Of the 144 samples collected, plastics were found at all locations and sample sites. Average density of 9669 plastic items/km 2, where 68 % were microplastics. Fragment and thread morphologies and polyethylene polymers were most common. Study data is useful for mitigation and remediation efforts.